2015
DOI: 10.2514/1.a32959
|View full text |Cite
|
Sign up to set email alerts
|

Best Geosynchronous Earth Orbit Daytime Spacecraft Charging Index

Abstract: Recently, the debate on what is the best daytime Geosynchronous Earth Orbit spacecraft charging index has been reopened. In this paper, the conclusions of one of the recent papers on the subject are verified by comparing Nascap-2k results with charging and fluxes measured on the Spacecraft Charging at the High Altitudes, Intelsat, Defense Satellite Communications System, and Los Alamos National Laboratory Geosynchronous Earth Orbit satellites. In addition, a refined measure of charging is presented as the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The best correlation with potentials is thus obtained for 10-50 keV electrons, which is consistent with the 8 keV and 9 keV electron temperature thresholds from Thomsen et al (2013) and from Ferguson et al (2015), respectively. Previous results showed that frame charging of the SCATHA spinning spacecraft correlated with the electron flux above the threshold temperature of 30 keV (Mullen et al, 1986).…”
Section: Statistical Resultssupporting
confidence: 76%
“…The best correlation with potentials is thus obtained for 10-50 keV electrons, which is consistent with the 8 keV and 9 keV electron temperature thresholds from Thomsen et al (2013) and from Ferguson et al (2015), respectively. Previous results showed that frame charging of the SCATHA spinning spacecraft correlated with the electron flux above the threshold temperature of 30 keV (Mullen et al, 1986).…”
Section: Statistical Resultssupporting
confidence: 76%
“…It has been established that the high flux of electrons with energies E ≥ 10 keV is the main factor leading to the hazardous level of surface charging (e.g Thomsen et al, 2013;Ferguson et al, 2015;Matéo-Vélez et al, 2018). It has been established that the high flux of electrons with energies E ≥ 10 keV is the main factor leading to the hazardous level of surface charging (e.g Thomsen et al, 2013;Ferguson et al, 2015;Matéo-Vélez et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also shown are the 10 keV (kilo-electron Volts) electron fluxes from the air force, aerospace, National Reconnaissance Office empirical trapped radiation climatology model (AE9/AP9/SPM), with a running mean to simulate charge conduction through the solar array cover glasses (in these cases, the exponential smoothing phasing [1] is maintained by a running mean or moving average of the same timescale). Although all electrons of energy > 9 keV contribute to charging [2], only the 10 keV fluxes are shown here, because the >10 keV fluxes show the same phasing. The right-hand scale is linear from zero at the bottom.…”
Section: Preliminary October Lanl Resultsmentioning
confidence: 99%